Anticipating Relations: Beyond Reciprocity and Obligation in the Ger Districts of Ulaanbaatar, Mongolia. Issue 1 (1st March 2019) - Fox, Elizabeth
Abstract : In the outskirts of Ulaanbaatar, known as ger districts, a growing number of rural-to-urban migrants live without access to formal urban infrastructure or regular incomes. Under these challenging material conditions, personal networks take precedence, providing and regulating access to employment and meat provisioning. Looking beyond discussions of anticipation among migrants focusing on the goals of migration, I interrogate the role of anticipation in the making and maintaining of relational networks. Existing analyses of such networks in Mongolia have generally relied on idioms of reciprocity or obligation. Focusing instead on material transfers and transactions among ger district residents reveals such networks to be more ambiguous and prone to failure than notions of reciprocity or obligation can easily accommodate. This article argues that the productive contradiction within the concept of anticipation – encompassing both expectative waiting and pre-emptive action – can illuminate new aspects of these relations and networks in action.